Quaternized oil-control composite powder, preparation method thereof and application of quaternized oil-control composite powder in oil-control cosmetics
By grafting quaternary ammonium polymers on porous inorganic minerals, the directional adsorption and rapid flocculation of oil secreted by the human body are achieved, and the problem of adsorbing oils and nutrients in existing oil-controlled cosmetics is solved, which extends the durability of makeup and is applicable. In different types of oil-control cosmetics.
Patent Information
- Application Number
- CN202411629887.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing oil-controlled cosmetics absorb oil secreted by the human body, and also absorb oily nutrients in cosmetics, and the makeup is maintained for a short time.
Using quaternary ammonium oil-controlled composite powder, the quaternary polymer is grafted on porous inorganic minerals, and the porous structure of the mineral and the electrostatic interaction between the quaternary ammonium salt and carboxylate are used to achieve directional adsorption and rapid flocculation of unsaturated fatty acids. Curing and adjusting the ratio of polymer monomers to regulate the hydrophilicity and hydrophobicity of the composite powder.
It realizes the selective adsorption of oil secreted by the human body, avoids adsorbing oily nutrients in cosmetics, extends the durability of the makeup, and is suitable for different types of oil-controlled cosmetics.
Smart Images

Figure CN119185080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cosmetics, and in particular relates to a quaternary ammonium oil-controlling composite powder and a preparation method thereof and application of the quaternary ammonium oil-controlling composite powder in oil-controlling cosmetics. Background Art
[0002] The human skin naturally secretes oil, especially in summer. Excessive sebum can cause makeup to fall off and affect the makeup effect, so the cosmetic system needs oil control function. Commonly used oil control cosmetics are porous oil control powders, such as porous silica and porous polymethyl methacrylate, but this porous oil control powder also has shortcomings. One reason is that this porous oil control powder does not have selective adsorption. While absorbing the oil secreted by the skin, it also absorbs the oily nutrients in the cosmetics; the second reason is that this porous oil control powder cannot flocculate and solidify the oil, which will result in the makeup effect not lasting long.
[0003] Therefore, it is of great significance for oil-control cosmetics to develop an oil-control powder that can directional absorb unsaturated fatty acids (the main oil component of human sweat) and has a good makeup-lasting effect and no safety risks. Summary of the invention
[0004] The purpose of the present invention is to solve the problem that the oil-controlling cosmetics in the prior art absorb the oil secreted by the human body and also absorb the oily nutrients in the cosmetics and the makeup lasts for a short time. The present invention provides a quaternary ammonium oil-controlling composite powder, a preparation method thereof and an application in oil-controlling cosmetics.
[0005] The technical solution of the present invention is as follows:
[0006] One of the purposes of the present invention is to provide a method for preparing a quaternary ammonium oil-controlling composite powder, the method comprising:
[0007] S1: adding porous mineral, surfactant, dispersant and water into a reactor, stirring evenly, adding metal salt, continuing stirring, then dropping ammonium bicarbonate aqueous solution, continuing the reaction, then washing and filtering twice, drying, and calcining in a muffle furnace to obtain a modified mineral composite powder;
[0008] S2: Dispersing the modified mineral composite powder of S1 in toluene, adding a silane coupling agent and a polymerization inhibitor, filtering and washing after the reaction is completed, and then filtering and drying to obtain a modified mineral composite powder with double bonds;
[0009] S3: Under nitrogen protection, the modified mineral composite powder with double bonds in S2, the polymerized monomer and toluene are mixed and stirred evenly, and then an initiator is added to react. After the reaction is completed, the powder is washed, filtered and dried to obtain a polymer-modified mineral composite powder;
[0010] S4: Under stirring conditions, the S3 polymer-modified mineral composite powder and toluene are mixed, and a halogenated hydrocarbon toluene solution is dropped into the mixture to carry out a quaternization reaction. After the reaction is completed, the mixture is filtered, washed, dried, and ball-milled at 30 rpm to obtain a quaternized oil-control composite powder.
[0011] It is further defined that the porous mineral of S1 is diatomaceous earth or zeolite, the surfactant is hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate or Tween, the dispersant is polyethylene glycol 200 or polyethylene glycol 400, the metal salt is zinc sulfate, aluminum sulfate, zinc nitrate, aluminum nitrate, zinc acetate or zinc chloride, the mass ratio of the surfactant to the porous mineral of S1 is 1-5:100, the mass ratio of the dispersant to the porous mineral is 1-5:100, the mass ratio of the metal salt to the porous mineral is 1:1-10, and the molar ratio of ammonium bicarbonate to the metal salt is 1-8: 1; the silane coupling agent of S2 is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl-tri(2-methoxyethoxy)silane or γ-(methacryloyloxy)propyl trimethoxysilane, the polymerization inhibitor is catechol, the mass ratio of the modified mineral composite powder of S2 to the silane coupling agent is 5-20:1, and the mass ratio of the polymerization inhibitor to the silane coupling agent is 1:50-200; the halogenated hydrocarbon of S4 is octadecane chloride, hexadecane chloride, hexadecane bromide or octadecane bromide, and the mass ratio of the S4 polymer-modified mineral composite powder to the halogenated hydrocarbon is 20:1-4.
[0012] It is further defined that the silica content of diatomaceous earth is greater than 75%, the particle size is 5-50 μm, and the porosity is 30-150 μm. 2 / g; the zeolite particle size is 5-50μm and the porosity is 150-300m 2 / g.
[0013] It is further defined that the polymerization monomer of S3 is a mixture of divinyl polydimethylsiloxane, terminal vinyl polyoxyethylene ether and dimethylaminoethyl methacrylate, the initiator is an azo initiator, the mass ratio of S3 modified mineral composite powder with double bonds to the polymerization monomer is 5-20:1, and the mass ratio of the initiator to the polymerization monomer is 1:10-50.
[0014] It is further defined that the azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile, and the mass ratio of divinyl polydimethylsiloxane, terminal vinyl polyoxyethylene ether and dimethylaminoethyl methacrylate is 0.1-2:0.1-5:1.
[0015] It is further defined that the stirring time of S1 is 0.5-2h, the continued stirring time is 0.5-2h, the continued reaction temperature is 50-80℃, the continued reaction time is 5-10h, the drying temperature is 80-120℃, the drying time is 6-12h, the calcination temperature is 350-500℃, and the calcination time is 2-6h; the reaction temperature of S2 is 50-100℃, the reaction time is 4-8h, the drying temperature is 50-80℃, and the drying time is 3-6h; the stirring time of S3 is 0.1-2h, the reaction temperature is 50-80℃, and the reaction time is 4-8h; the reaction temperature of S4 is 80-100℃, and the reaction time is 4-8h.
[0016] The second object of the present invention is to provide a hydrophobic quaternary ammonium oil-control composite powder prepared by the above preparation method, wherein the content of divinyl polydimethylsiloxane in the polymerization monomer of the hydrophobic quaternary ammonium oil-control composite powder is ≥20wt.%.
[0017] The third object of the present invention is to provide a hydrophilic quaternary ammonium oil-controlling composite powder prepared by the above-mentioned preparation method, wherein the content of divinyl polydimethylsiloxane in the polymerization monomer of the hydrophilic quaternary ammonium oil-controlling composite powder is less than 20wt.%.
[0018] A fourth object of the present invention is to provide a use of the above-mentioned hydrophobic quaternary ammonium oil-control composite powder in oil-soluble oil-control cosmetics.
[0019] A fifth object of the present invention is to provide a use of the above-mentioned hydrophilic quaternary ammonium oil-control composite powder in water-soluble oil-control cosmetics.
[0020] Compared with the prior art, the specific advantages of the present invention are as follows:
[0021] The quaternized oil-controlling composite powder provided by the present invention can be applied to the directional adsorption of oils and fats. The present invention uses porous inorganic minerals as carriers, and grafts quaternized polymers on the porous minerals to form a quaternized oil-controlling composite powder with a stable structure. The composite powder makes full use of the porous structure of the mineral and the electrostatic interaction between the quaternary ammonium salt and the carboxylate radical, adsorbs and fixes the unsaturated fatty acids secreted by the human body in the porous structure of the mineral, and quickly flocculates and solidifies the unsaturated fatty acids. In addition, by changing the comonomer structure, the hydrophilicity and hydrophobicity of the quaternized oil-controlling composite powder can be regulated, thereby meeting the application requirements of different types of oil-controlling cosmetics. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the infrared spectrum of the quaternized oil-controlling composite powder prepared in Example 1;
[0023] Figure 2 This is a scanning electron micrograph of the quaternized oil-controlling composite powder prepared in Example 1;
[0024] Figure 3This is a contact angle test diagram of the quaternized oil-control composite powder prepared in Example 1. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0026] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0027] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.
[0028] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.
[0029] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0030] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0031] The endpoints and any values of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.
[0032] Embodiment 1:
[0033] S1: Weigh 50g of diatomaceous earth with a particle size of 10μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them to a reactor and stir for 1h, weigh 25g of zinc sulfate, add them to a reactor and stir for 1h, weigh 25g of ammonium bicarbonate and dissolve them in 50g of water to form an aqueous solution of ammonium bicarbonate, and drip the aqueous solution of ammonium bicarbonate into the reactor under stirring. After the dripping is completed, react at 60°C for 6h, then filter and wash, add the obtained filter cake and 500mL of anhydrous ethanol to the reactor, stir for 1h, and then filter, and bake the obtained solid powder in an oven at 100°C for 8h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified diatomaceous earth composite powder;
[0034] S2: Weigh 50 g of modified diatomite composite powder and 500 mL of toluene into a reactor, then add 5 g of vinyltrimethoxysilane and 0.05 g of catechol, react at 80 ° C for 6 h, then filter, wash with ethanol, and filter again. The obtained sample is dried in an oven at 60 ° C for 5 h to obtain a modified diatomite composite powder with double bonds;
[0035] S3: Under nitrogen protection, 50g of modified diatomite composite powder with double bonds, 1g of divinyl polydimethylsiloxane, 2g of terminal vinyl polyoxyethylene ether, 2g of dimethylaminoethyl methacrylate and 500g of toluene were added to the reactor, stirred for 0.5h, and then 0.24g of azobisisobutyronitrile was added, and the reaction was continued at 60°C for 6h, and then filtered, washed and dried to obtain a polymer-modified diatomite composite powder;
[0036] S4: 50g of polymer-modified diatomite composite powder and 500g of toluene were weighed and added to the reactor, and 3.6g of chlorooctadecane was weighed and dissolved in 10mL of toluene to form a toluene solution of chlorooctadecane. Under stirring, the toluene solution of chlorooctadecane was added dropwise to the reactor, refluxed at 90°C for 6h, and quaternized, filtered, washed, dried, and then ball-milled at 30rpm to obtain a quaternized oil-control composite powder.
[0037] Embodiment 2:
[0038] S1: Weigh 50g of diatomite with a particle size of 20μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them to the reactor and stir for 1h, weigh 25g of zinc sulfate, add them to the reactor and stir for 1h. Then weigh 30g of ammonium bicarbonate and dissolve it in 50g of water to form an aqueous solution of ammonium bicarbonate. Under stirring conditions, drop the aqueous solution of ammonium bicarbonate into the reactor. After the dropwise addition is completed, react at 60°C for 6h, then filter and wash, add the obtained filter cake and 500ml of anhydrous ethanol to the reactor and stir for 1h, then filter again, bake the obtained solid powder in an oven at 100°C for 8h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified diatomite composite powder;
[0039] S2: Weigh 50 g of modified diatomite composite powder and 500 ml of toluene into a reactor, then add 3.0 g of γ-(methacryloyloxy)propyltrimethoxysilane and 0.05 g of catechol, react at 80 ° C for 6 h, then filter, wash with ethanol, and filter again. The obtained sample is dried in an oven at 60 ° C for 5 h to obtain a modified diatomite composite powder with double bonds;
[0040] S3: Under nitrogen protection, 50 g of modified diatomite composite powder with double bonds, 1 g of divinyl polydimethylsiloxane, 7.5 g of terminal vinyl polyoxyethylene ether, 1.5 g of dimethylaminoethyl methacrylate and 500 g of toluene were added to the reactor, mechanically stirred for 0.5 h, and then 0.24 g of azobisisobutyronitrile was added, and the reaction was continued at 60 ° C for 6 h, and then filtered, washed and dried to obtain a polymer-modified diatomite composite powder;
[0041] S4: 50g of polymer-modified diatomite composite powder and 500g of toluene were weighed and added to the reactor. 4g of octadecane bromide was weighed and dissolved in 10ml of toluene to form a toluene solution of octadecane bromide. Under stirring, the toluene solution of octadecane bromide was added dropwise to the reactor, refluxed at 90°C for 6h, and quaternized. After the reaction, the mixture was filtered, washed, dried, and then ball-milled at 30rpm to obtain a quaternized oil-control composite powder.
[0042] Embodiment 3:
[0043] S1: Weigh 50g of diatomite with a particle size of 50μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them to the reactor and stir for 1h, weigh 40g of zinc sulfate, add them to the reactor and stir for 1h. Then weigh 50g of ammonium bicarbonate and dissolve it in 50g of water to form an aqueous solution of ammonium bicarbonate. Under stirring conditions, drop the aqueous solution of ammonium bicarbonate into the reactor. After the dropwise addition is completed, react at 60°C for 6h, then filter and wash, add the obtained filter cake and 500ml of anhydrous ethanol to the reactor and stir for 1h, then filter again, bake the obtained solid powder in an oven at 100°C for 10h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified diatomite composite powder;
[0044] S2: Weigh 50 g of modified diatomite composite powder and 500 ml of toluene into a reactor, then add 8.0 g of γ-(methacryloyloxy)propyltrimethoxysilane and 0.05 g of catechol, react at 80 ° C for 6 h, then filter, wash with ethanol, and filter again. The obtained sample is dried in an oven at 60 ° C for 5 h to obtain a modified diatomite composite powder with double bonds;
[0045] S3: Under nitrogen protection, 50 g of modified diatomite composite powder with double bonds, 3.5 g of divinyl polydimethylsiloxane, 0.5 g of terminal vinyl polyoxyethylene ether, 4 g of dimethylaminoethyl methacrylate and 500 g of toluene were added to the reactor, mechanically stirred for 0.5 h, and then 0.24 g of azobisisobutyronitrile was added, and the reaction was continued at 60 ° C for 6 h, and then the reaction solution was filtered, washed and dried to obtain a polymer-modified diatomite composite powder;
[0046] S4: Weigh 50g of polymer-modified diatomite composite powder and 500g of toluene and add them to the reactor. Weigh 4g of hexadecane bromide and dissolve it in 10ml of toluene to form a toluene solution of hexadecane bromide. Under stirring, add the toluene solution of hexadecane bromide dropwise to the reactor, reflux at 90°C for 6h, and perform quaternization reaction. After the reaction is completed, filter, wash, dry, and then ball mill at 30rpm to obtain a quaternized oil-control composite powder.
[0047] Embodiment 4:
[0048] S1: Weigh 50g of diatomaceous earth with a particle size of 10μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them into a reactor and stir for 1h, weigh 6g of zinc sulfate, add them into the reactor and stir for 1h, then weigh 8g of ammonium bicarbonate and dissolve it in 50g of water to form an aqueous solution of ammonium bicarbonate, under stirring, drop the aqueous solution of ammonium bicarbonate into the reactor, react at 60°C for 6h after the dropwise addition is completed, then filter and wash, add the obtained filter cake and 500ml of anhydrous ethanol into the reactor and stir for 1h, then filter again, and bake the obtained solid powder in an oven at 100°C for 10h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified diatomaceous earth composite powder;
[0049] S2: Weigh 50 g of modified diatomite composite powder and 500 ml of toluene into a reactor, then add 3.5 g of γ-(methacryloyloxy)propyltriethoxysilane and 0.05 g of catechol, react at 80 ° C for 6 h, then filter, wash with ethanol, and filter again. The obtained sample is dried in an oven at 60 ° C for 5 h to obtain a modified diatomite composite powder with double bonds;
[0050] S3: Under nitrogen protection, 50 g of modified diatomite composite powder with double bonds, 0.5 g of divinyl polydimethylsiloxane, 0.5 g of terminal vinyl polyoxyethylene ether, 5 g of dimethylaminoethyl methacrylate and 500 g of toluene were added to the reactor, mechanically stirred for 0.5 h, and then 0.24 g of azobisisobutyronitrile was added, and the reaction was continued at 60 ° C for 6 h, and then filtered, washed and dried to obtain a polymer-modified diatomite composite powder;
[0051] S4: Weigh 50g of polymer-modified diatomaceous earth composite powder and 500g of toluene into a reactor, weigh 6.5g of hexadecane chloride and dissolve it in 10ml of toluene to form a toluene solution of hexadecane chloride. Under stirring, drop the toluene solution of hexadecane chloride into the reactor, reflux at 90°C for 6h to carry out quaternization reaction, filter after the reaction, wash, dry, and then ball mill at 30rpm to obtain a quaternized oil-control composite powder.
[0052] Embodiment 5:
[0053] S1: Weigh 50g of zeolite powder with a particle size of 10μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them into a reactor and stir for 1h, weigh 25g of zinc nitrate, add them into a reactor and stir for 1h, then weigh 30g of ammonium bicarbonate and dissolve it in 50g of water to form an ammonium bicarbonate aqueous solution, add the ammonium bicarbonate aqueous solution dropwise into the reactor under stirring, react at 60°C for 6h after the addition is completed, then filter and wash, add the obtained filter cake and 500ml of anhydrous ethanol into the reactor and stir for 1h, then filter again, and bake the obtained solid powder in an oven at 100°C for 8h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified zeolite composite powder;
[0054] S2: Weigh 50 g of modified zeolite composite powder and 500 ml of toluene into a reactor, then add 3.0 g of vinyl-tri(2-methoxyethoxy)silane and 0.05 g of catechol, react at 80° C. for 6 h, then filter, wash with ethanol, and filter again. The obtained sample is dried in an oven at 60° C. for 5 h to obtain a modified zeolite composite powder with double bonds;
[0055] S3: Under nitrogen protection, 50 g of modified zeolite composite powder with double bonds, 1 g of divinyl polydimethylsiloxane, 7.5 g of terminal vinyl polyoxyethylene ether, 1.5 g of dimethylaminoethyl methacrylate and 500 g of toluene were added to the reactor, mechanically stirred for 0.5 h, and then 0.24 g of azobisisobutyronitrile was added, and the reaction was continued at 60 ° C for 6 h, and then filtered, washed and dried to obtain a polymer-modified zeolite composite powder;
[0056] S4: Weigh 50g of polymer-modified zeolite composite powder and 500g of toluene and add them to the reactor. Weigh 4g of octadecane bromide and dissolve it in 10ml of toluene to form a toluene solution of octadecane bromide. Under stirring, drip the toluene solution of octadecane bromide into the reactor, reflux at 90°C for 6h, and perform quaternization reaction. After the reaction is completed, filter, wash, dry, and then ball mill at 30rpm to obtain a quaternized oil-control composite powder.
[0057] Embodiment 6:
[0058] S1: Weigh 50g of zeolite powder with a particle size of 20μm, 2g of hexadecyltrimethylammonium bromide, 2g of polyethylene glycol 400 and 500mL of water, add them into a reactor and stir for 1h, weigh 40g of aluminum sulfate, add them into a reactor and stir for 1h, then weigh 60g of ammonium bicarbonate and dissolve it in 50g of water to form an ammonium bicarbonate aqueous solution, under stirring, drop the ammonium bicarbonate aqueous solution into the reactor, react at 60°C for 6h after the dropwise addition, then filter and wash, add the obtained filter cake and 500ml of anhydrous ethanol into the reactor and stir for 1h, then filter, and bake the obtained solid powder in an oven at 100°C for 8h, and then calcine in a muffle furnace at 400°C for 4h to obtain a modified zeolite composite powder;
[0059] S2: Weigh 50g of modified zeolite composite powder and 500ml of toluene into a reactor, then add 8.0g of γ-(methacryloyloxy)propyltrimethoxysilane and 0.05g of catechol, react at 80°C for 6h, then filter, wash with ethanol, filter again, and dry the obtained sample in an oven at 60°C for 5h to obtain a modified zeolite composite powder with double bonds;
[0060] S3: Under nitrogen protection, 50 g of modified zeolite composite powder with double bonds, 3.5 g of divinyl polydimethylsiloxane, 0.5 g of terminal vinyl polyoxyethylene ether, 4 g of dimethylaminoethyl methacrylate and 500 g of toluene were added to the reactor, mechanically stirred for 0.5 h, and then 0.24 g of azobisisobutyronitrile was added, and the reaction was continued at 60 ° C for 6 h, and then filtered, washed and dried to obtain a polymer-modified zeolite composite powder;
[0061] S4: Weigh 50g of polymer-modified zeolite composite powder and 500g of toluene and add them to the reactor. Weigh 4g of hexadecane bromide and dissolve it in 10ml of toluene to form a toluene solution of hexadecane bromide. Under stirring, drip the toluene solution of hexadecane bromide into the reactor, reflux at 90°C for 6h, and perform quaternization reaction. After the reaction is completed, filter, wash, dry, and then ball mill at 30rpm to obtain a quaternized oil-control composite powder.
[0062] Comparative Example 1:
[0063] The difference between Comparative Example 1 and Example 1 is that step 1 is omitted, and 5 g of ZnO and 35 g of diatomaceous earth with a particle size of 10 μm are blended to obtain a mixture that replaces the modified diatomaceous earth composite powder.
[0064] Comparative Example 2:
[0065] The difference between Comparative Example 2 and Example 1 is that step 4 is omitted and no quaternization treatment is performed.
[0066] Comparative Example 3:
[0067] The difference between Comparative Example 3 and Example 1 is that 10 μm solid silica microspheres are used instead of diatomaceous earth.
[0068] Figure 1 This is the infrared spectrum of the quaternized oil-controlling composite powder prepared in Example 1. It can be seen from the figure that at 2800cm -1 The characteristic peak of quaternary ammonium group appeared at , indicating that the quaternization of polymer on the surface of composite powder was successful.
[0069] Figure 2This is a scanning electron microscope image of the quaternized oil-controlling composite powder prepared in Example 1. It can be seen from the figure that the surface of the quaternized oil-controlling composite powder is rough and has mesopores, proving that the porous structure of the diatomaceous earth itself is not blocked by a series of operations in this experiment, and the electrostatic interaction between the quaternary ammonium salt grafted on the diatomaceous earth in this experiment and the carboxylate radical can be utilized to adsorb and fix the unsaturated fatty acids secreted by the human body in the porous structure of the diatomaceous earth, thereby achieving the effect of adsorbing oil.
[0070] Oil absorption test:
[0071] 4 g of the final oil-control powder was weighed from Examples 1-6 and Comparative Examples 1-3, respectively, and mixed evenly with 40 g of oleic acid and 40 g of silicone oil (10 cst), respectively, and allowed to stand at room temperature for 18 h, then 100 ml of petroleum ether was added, mixed for 30 min, rinsed and filtered, and the residue was calcined at 500 ° C to determine the strong heat loss. The results are shown in Table 1.
[0072] Flocculation solidification test:
[0073] 2 g of the final oil-control powder was weighed from Examples 1-6 and Comparative Examples 1-3, and 6 g of water and 12 g of oleic acid were added to a glass bottle to prepare simulated artificial sebum. The bottle was shaken up and down rapidly and vigorously for more than 20 times, then allowed to stand, and the glass bottle was gently inverted to observe its fluidity, and the system solidification time was recorded. The results are shown in Table 1.
[0074] Water absorption test:
[0075] 4 g of the final oil-control powder was weighed from Examples 1-6 and Comparative Examples 1-3, respectively, and mixed evenly with 40 g of water, respectively, and allowed to stand at room temperature for 18 h, then filtered, and the residue was calcined at 500° C. to determine the heat loss. The results are shown in Table 1.
[0076] Table 1: Experimental table of oil absorption, contact angle and flocculation solidification results of Examples 1-6 and Comparative Examples 1-3
[0077]
[0078]
[0079] As shown in Table 1, the quaternary ammonium oil-control composite powder prepared by the experimental method has high adsorption to oleic acid, and can quickly flocculate and solidify artificial sebum, so as to achieve the effect of effective oil control and makeup maintenance of cosmetics. Moreover, the quaternary ammonium oil-control composite powder prepared by the experimental method can adjust the hydrophilicity and hydrophobicity of the surface of the quaternary ammonium oil-control composite powder by adjusting the ratio of the three polymerized monomers added. When the quaternary ammonium oil-control composite powder exhibits hydrophilicity, it can be added to water-soluble oil-control cosmetics. When the quaternary ammonium oil-control composite powder exhibits hydrophobicity, it can be added to non-water-soluble oil-control cosmetics, so that the quaternary ammonium oil-control composite powder prepared in this experiment can meet different application scenarios.
[0080] Selective adsorption test:
[0081] Weigh 0.1g of different types of oils and fats, add 100mL of n-hexane to dissolve, and mix well. Weigh 0.5g of the quaternized oil-controlling composite powder prepared in Example 1 into a conical flask, add 50mL of n-hexane containing oils and fats, seal with a lid, shake for 1h, filter, and then analyze by GCMS. The results are shown in Table 2:
[0082] Table 2: Selective adsorption test table of the quaternized oil-control composite powder prepared in Example 1
[0083] Types of Grease Adsorption amount (%) Oleic acid 46.1 White oil 1.1 Silicone oil 1.6 Caprylic Capric Triglyceride 2.1 Squalane 0.4
[0084] From Table 2, we can see that the quaternized oil-controlling composite powder prepared by the present invention can selectively absorb oleic acid secreted by the human body, but will not absorb white oil, silicone oil, caprylic capric triglyceride and squalane added in cosmetics, which are oily substances for protecting the skin. This shows that the experiment successfully prepared an oil-controlling composite powder with selective adsorption, which is of great significance to the development and production of oil-controlling composite powder cosmetics.
[0085] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a quaternary ammonium oil-controlling composite powder, characterized in that: The method: S1: adding porous mineral, surfactant, dispersant and water into a reactor, stirring evenly, adding metal salt, continuing stirring, then dropping ammonium bicarbonate aqueous solution, continuing the reaction, then washing and filtering twice, drying, and calcining in a muffle furnace to obtain a modified mineral composite powder; S2: Dispersing the modified mineral composite powder of S1 in toluene, adding a silane coupling agent and a polymerization inhibitor, filtering and washing after the reaction is completed, and then filtering and drying to obtain a modified mineral composite powder with double bonds; S3: Under nitrogen protection, the modified mineral composite powder with double bonds in S2, the polymerized monomer and toluene are mixed and stirred evenly, and then an initiator is added to react. After the reaction is completed, the powder is washed, filtered and dried to obtain a polymer-modified mineral composite powder; S4: Under stirring conditions, the S3 polymer-modified mineral composite powder and toluene are mixed, and a halogenated hydrocarbon toluene solution is dropped into the mixture to carry out a quaternization reaction. After the reaction is completed, the mixture is filtered, washed, dried, and ball-milled at 30 rpm to obtain a quaternized oil-control composite powder.
2. The method according to claim 1, characterized in that The porous mineral of S1 is diatomaceous earth or zeolite, the surfactant is hexadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate or Tween, the dispersant is polyethylene glycol 200 or polyethylene glycol 400, the metal salt is zinc sulfate, aluminum sulfate, zinc nitrate, aluminum nitrate, zinc acetate or zinc chloride, the mass ratio of the surfactant to the porous mineral of S1 is 1-5:100, the mass ratio of the dispersant to the porous mineral is 1-5:100, the mass ratio of the metal salt to the porous mineral is 1:1-10, and the molar ratio of ammonium bicarbonate to the metal salt is 1-8:1; S The silane coupling agent of 2 is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl-tri(2-methoxyethoxy)silane or γ-(methacryloyloxy)propyl trimethoxysilane, the polymerization inhibitor is catechol, the mass ratio of the modified mineral composite powder of S2 to the silane coupling agent is 5-20:1, and the mass ratio of the polymerization inhibitor to the silane coupling agent is 1:50-200; the halogenated hydrocarbon of S4 is octadecane chloride, hexadecane chloride, hexadecane bromide or octadecane bromide, and the mass ratio of the S4 polymer modified mineral composite powder to the halogenated hydrocarbon is 20:1-4.
3. The method according to claim 2, characterized in that The silica content of diatomite is greater than 75%, the particle size is 5-50μm, and the porosity is 30-150m 2 / g; the zeolite particle size is 5-50μm and the porosity is 150-300m 2 / g.
4. The method according to claim 1, characterized in that: The polymerization monomer of S3 is a mixture of divinyl polydimethylsiloxane, terminal vinyl polyoxyethylene ether and dimethylaminoethyl methacrylate, the initiator is an azo initiator, the mass ratio of S3 modified mineral composite powder with double bonds to the polymerization monomer is 5-20:1, and the mass ratio of initiator to polymerization monomer is 1:10-50.
5. The method according to claim 4, characterized in that The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile, and the mass ratio of divinyl polydimethylsiloxane, terminal vinyl polyoxyethylene ether and dimethylaminoethyl methacrylate is 0.1-2:0.1-5:
1.
6. The method according to claim 1, characterized in that S1 stirring time is 0.5-2h, continue stirring time 0.5-2h, continue reaction temperature 50-80℃, continue reaction time 5-10h, drying temperature 80-120℃, drying time 6-12h, calcination temperature 350-500℃, calcination time 2-6h; S2 reaction temperature 50-100℃, reaction time 4-8h, drying temperature 50-80℃, drying time 3-6h; S3 stirring time 0.1-2h, reaction temperature 50-80℃, reaction time 4-8h; S4 reaction temperature 80-100℃, reaction time 4-8h.
7. The hydrophobic quaternary ammonium oil-controlling composite powder prepared by the method according to any one of claims 1 to 6, characterized in that: The content of divinyl polydimethylsiloxane in the polymerized monomer is ≥20wt.%.
8. The hydrophilic quaternary ammonium oil-controlling composite powder prepared by the method according to any one of claims 1 to 6, characterized in that: The content of divinyl polydimethylsiloxane in the polymerized monomer is less than 20 wt.%.
9. Use of the hydrophobic quaternary ammonium oil-controlling composite powder according to claim 7 in oil-soluble cosmetics.
10. Use of the hydrophilic quaternary ammonium oil-controlling composite powder according to claim 8 in water-soluble cosmetics.
Citation Information
Patent Citations
Preparation method of dimethyl diallyl ammonium chloride-modified porous diatomaceous earth
CN105727903A
Composite acid conditioning mud film
CN118121506A
Long-acting oil-control non-drying modified composite powder and preparation method thereof
CN118286111A
Hair nourishing and hair growing agent
JP1994321737A
Cosmetic composition for adsorbing volatile organic compound containing mesoporous materials
KR1020100059031A
